(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Lexico-syntactical stylistic devices addresses the significance and application of linguistic and stylistic tools that encompass both vocabulary and syntax to achieve specific rhetorical and expressive effects in language and literature. The annotation explores the range of devices such as repetition, alliteration, inversion, parallelism, and more, unveiling their impact on literary and rhetorical composition. It also delves into the historical, cross-cultural, and contemporary usage of these devices, shedding light on their diverse applications and interpretations. Furthermore, the annotation highlights the educational and pedagogical value of these stylistic devices, emphasizing their role in language arts education and literacy development. Overall, the annotation constructs a framework for understanding the pivotal role of lexico-syntactical stylistic devices in language, literature, and communication, while advocating for their continued exploration and integration across various linguistic and literary contexts.